Spiral computed tomographic demonstration of C-shaped canals in mandibular second molars - MUMCU, GONCA; KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (BRITISH INST RADIOLOGY, 2005)
Objectives: The aim of this study was to evaluate the prevalence of C-shaped canals in single rooted mandibular second molars with spiral computed tomographic imaging in detail. Methods: One hundred and twelve single-rooted mandibular second molar samples were selected from 491 extracted mandibular second molars. The teeth were scanned by spiral computed tomographic technique to examine canal configurations. Results: The evaluation criteria of the shape of roots was based on Manning's category as round, oval and C-shaped. The prevalence of C-shaped canals was found to be 8. 1 % in mandibular second molars. The evaluation of the root canal configurations of C-shaped mandibular second molars with single roots (40 teeth) was based on Vertucci's classification. Vertucci type 1 canals were most frequently seen in C-shaped mandibular second molars (40%). Additionally, we disclosed three additional canal types. Conclusion: Results of this study demonstrated that high resolution visualization of the root canal shape can be achieved by spiral computed tomographic imaging.
Keywords: spiral computed tomography; C-shaped canals; mandibular second molars; ROOT CANALS; CHINESE POPULATION; ANATOMY; OBTURATION; 2ND-MOLARS; MORPHOLOGY; FEATURES; SYSTEM